INTRA-REGIONAL DIFFERENTIATION OF ENTREPRENEURSHIP OF MUNICIPALITIES OF THE ŚWIĘTOKRZYSKIE VOIVODESHIP IN TERMS OF SUSTAINABLE DEVELOPMENT IN 2010 AND 2020 - Paweł Dziekański; Łukasz Popławski; Fabio Fragomeni (Baltic Journal of Economic Studies)
Regions, as spatial socio-economic systems, are characterised by different levels of development and entrepreneurship. Entrepreneurship is an element of job creation, economic development and innovation. It is an element of local territorial capital and a development factor, an element that shapes both the structures of economies and their communities, a determinant of their sustainable development. The phenomenon of entrepreneurship is influenced by a number of factors, including social capital, demographic characteristics, the availability of infrastructure, access to natural resources, the economic structures prevailing in a given region, the quality of human capital, the standard of housing stock, and the quality of infrastructure facilities. The objective of this article is to assess the economic and demographic factors that contribute to the spatial differentiation of the entrepreneurial situation of municipalities, based on a synthetic measure. The empirical data were collected at the municipal level in the Świętokrzyskie region of Poland. The variables were selected based on the availability of data from Statistics Poland for the years 2010 and 2020. Synthetic measures were constructed using the Technique for Order Preference by Similarity to an Ideal Solution method. The Świętokrzyskie region is distinguished by a notable lack of economic competitiveness. The synthetic measure of entrepreneurship in the municipalities of the Świętokrzyskie region exhibited a range of 0.27 to 0.75 in 2010 and 0.30 to 0.65 in 2020. The diversity of the municipalities is attributable to a range of factors, including demographic, natural and socio-economic development processes. It is evident that additional support is required to facilitate the growth and development of entrepreneurship in the Świętokrzyskie province. Spatial polarisation in terms of entrepreneurial development is correlated with demographic and economic variables. Municipalities within the sphere of influence of urban centres had favourable conditions for the development of entrepreneurship. Municipalities with an agricultural character, located on the periphery of Kielce and other cities in the region, have the least favourable conditions for the development of entrepreneurship. The growth of entrepreneurship has mainly taken place in centres with long service or industrial traditions. Concurrently, a more pronounced expansion of services was witnessed in urban areas situated at a distance from the central hubs, driven by the necessity to address the demands of the local population. Conversely, industrialisation flourished in cities in close proximity to these central locations, where extensive collaboration and convenient transportation networks were feasible. Ongoing studies of entrepreneurship and the variables that shape it, such as demographics, should help authorities to evaluate and change policies. The rise or fall of synthetic measures should be a way of assessing the impact of current regional management. The results obtained can inform local authorities about the disparities that exist between units.